The Role of Influencers in Shaping Public Opinion: A Study of Millennials and Gen Z - Sulistya A, Astrid; Yuningsih, Siti Hadiaty; Vaidyanatahan, Sundarapandian (International Journal of Linguistics, Communication, and Broadcasting, 2025)
The rise of social media has transformed the formation of public opinion, with digital influencers emerging as key actors in shaping attitudes, behaviors, and cultural trends. This study investigates the role of influencers in influencing Millennials and Generation Z, focusing on credibility, engagement, and generational differences. A mixed-methods approach was employed, combining a quantitative survey of 300 respondents (150 Millennials, 150 Gen Z) with in-depth interviews of 20 participants. Quantitative findings indicate that influencer credibility is the most significant factor for both generations, with over 70% of respondents citing trust and reputation as primary reasons for engagement. Both Millennials and Gen Z are influenced in lifestyle and consumption decisions; However, Gen Z shows greater susceptibility to socio-political narratives, whereas Millennials engage more critically and selectively. Qualitative analysis reveals four key themes: Millennials prioritize authenticity and transparency, while Gen Z exhibits strong emotional attachment through parasocial relationships and perceives influencers as role models and alternative sources of information. The findings underscore that influencers function not only as marketing agents but also as social actors and cultural mediators. Effective communication strategies must consider generational distinctions: authentic storytelling resonates with Millennials, while content emphasizes diversity, inclusivity, and social responsibility appeals to Gen Z. The study also highlights risks associated with misinformation and biased narratives, considering the need for ethical practices and enhanced digital literacy among both influencers and audiences. Overall, this research contributes to understanding how influencer culture shapes public opinion, revealing the multidimensional role of influencers in contemporary digital communication.